Implications for Brazil of the July 2008 draft agricultural modalities - Nassar, André Meloni; Cabral da Costa, Cinthia; Chiodi, Luciane (International Centre for Trade and Sustainable Development, 2008)
This study has shown that the proposed caps, with the exception of cotton, can constrain price suppression in situations of very low world prices. However, caps will not be effective if prices are at more normal levels. Brazil’s market access gains in developed countries are most likely to be constrained by the continuation of the SSG and the extent to which disciplines will achieve effective TRQ expansion. The continuation of the SSG will be an escape clause for countries seeking to maintain protection for specific sectors. The SSG will thus provide an additional layer of protection over and above the TRQ system, which itself is already a protectionist measure. Taking as an example the cases of beef, chicken and sugar in the EU, the compensation to be provided for selecting these products as sensitive will not be enough to create new trade. TRQ expansion will, at most, internalize over-quota trade: because there will not be any meaningful results in terms of import price reduction, imports will not increase. A reduction in over-quota tariffs would be the most effective way to create new trade. In the case of developing countries, the SSM is the central concern. There is a potential risk of increasing levels of protection beyond the tariff levels that were bound in the Uruguay Round leading to deterioration in current market access opportunities. Two topics now appear as “deal-breakers” for Brazil: the creation of new tariff rate quotas that will not be effective in creating new market access opportunities and an SSM that will lead to an increase in the level of protection consolidated before the Doha Round